Boundedness and Lagrange stability of fractional order perturbed system related to unperturbed systems with initial time difference in Caputo's sense - Yakar, Coskun; Cicek, Muhammed; Gucen, Mustafa Bayram (SPRINGER INTERNATIONAL PUBLISHING AG, 2011)
In this paper, we have investigated that initial time difference boundedness criteria and Lagrange stability for fractional order differential equation in Caputo's sense are unified with Lyapunov-like functions to establish comparison result. The qualitative behavior of a perturbed fractional order differential equation with Caputo's derivative that differs in initial position and initial time with respect to the unperturbed fractional order differential equation with Caputo's derivative has been investigated. We present a comparison result that again gives the null solution a central role in the comparison fractional order differential equation when establishing initial time difference boundedness criteria and Lagrange stability of the perturbed fractional order differential equation with respect to the unperturbed fractional order differential equation in Caputo's sense. AMS(MOS) Subject Classification: 34C11; 34D10; 34D99.
Keywords: initial time difference (ITD); boundedness and Lagrange stability; fractional order differential equation; perturbed fractional order differential systems; comparison results; CRITERIA; TERMS; Mathematics